Enhancing Efficiency and Equity : Challenges and Reform Opportunities Facing Health and Pension Systems in the Western Balkans - Bredenkamp, Caryn; Gragnolati, Michele; Ramljak, Vedad (World Bank, Washington, DC, 2013)
This collection of papers explores the major challenges to the sustainability of health and pension system financing in the countries of the Western Balkans - Albania, Bosnia and Herzegovina, the Former Yugoslav Republic of Macedonia, Montenegro, Serbia, and the province of Kosovo. It focuses on how the incentives created by the different elements of the financing arrangements affect the behavior of providers and individuals, and the resulting inefficiencies in revenue collection and expenditure containment. The volume commences with an analysis of healthcare financing, exploring patterns of healthcare expenditure, and examining the key drivers of current healthcare expenditure and the most significant barriers to revenue generation. Subsequent chapters give special attention to provider payment mechanisms and the pharmaceutical sector. Equity considerations are highlighted in a chapter that explores the protection that is offered against the financial impact of health expenditures. With respect to the pension sector, the volume provides an overview of national pension systems and outlines the main challenges to achieving a sustainable balance between pension benefits and costs. The analyses of the health and pension reform process are placed within the context of the labor market challenges in the sub-region, especially as they relate to the ability to raise revenue for health and pensions through payroll contributions. All chapters conclude by identifying some reforms that countries in the sub-region could consider in order to enhance the efficiency and sustainability of their systems. Data are drawn from international databases, country institutions, and household surveys.